1994
DOI: 10.1002/j.1467-8438.1994.tb00999.x
|View full text |Cite
|
Sign up to set email alerts
|

The reflecting team as a reflection of second order therapeutic ideals

Abstract: The reflecting (R.T.) team is examined within its theoretical, therapeutic and training contexts. A distinction is made between the reflecting team technique (R. T. T.) and the reflecting team process (R. T.P.), in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…By observing, recognising, intervening and making adjustments to practice, the therapist is able to respond in the moment, drawing from existing theoretical and clinical knowledge to improve the situation at hand. The literature on live supervision (Hunt & Sharpe, 2008;Lowe, Hunt & Simmons, 2008) and 'Reflective Team Process' (Anderson, 1987;Perlesz, Young, Paterson & Bridge, 1994) provides examples of how therapists integrate in the process of therapy by adopting multiple positions of both observer and facilitator. Reflection-on-practice occurs after the event and is retrospective.…”
Section: Reflectivity In Supervisionmentioning
confidence: 99%
“…By observing, recognising, intervening and making adjustments to practice, the therapist is able to respond in the moment, drawing from existing theoretical and clinical knowledge to improve the situation at hand. The literature on live supervision (Hunt & Sharpe, 2008;Lowe, Hunt & Simmons, 2008) and 'Reflective Team Process' (Anderson, 1987;Perlesz, Young, Paterson & Bridge, 1994) provides examples of how therapists integrate in the process of therapy by adopting multiple positions of both observer and facilitator. Reflection-on-practice occurs after the event and is retrospective.…”
Section: Reflectivity In Supervisionmentioning
confidence: 99%
“…A comprehensive account of a team that specialises in Family Therapy with the Deaf has been written by Warner (in press), and includes a detailed review of the literature. The team itself consists of both Deaf and hearing therapists and uses the Reflecting Team model originally described by Andersen (1987) and more recently reviewed by Perlesz, Young, Paterson, and Bridge (1994). This entails the use of a one-way mirror and the opportunity for the family to swop places with the team to observe their reflections.…”
Section: Family Therapymentioning
confidence: 99%
“…They also remind us that many clients want advice from their therapist, and that planning and strategy may have a useful part to play in giving clients what they want. Indeed, the transcript of the single-case study by Perlesz et al(1994) suggests that some clients want far more clarity and direction than is provided by the reflecting team. Smith et al (1994) studied the perceptions of couples and therapists of a reflecting team approach, and found that the couples were appreciative of the boundary between the observing team and the therapeutic system, with one party listening while the other was talking.…”
Section: Understanding Alliances 57mentioning
confidence: 99%